Detrimental influence of catalyst seeding on the device properties of CVD-grown 2D layered materials : a case study on MoSe2 - Xiong, Qihua (2015)
Seed catalyst such as perylene-3,4,9,10-tetracarboxylic acid tetrapotassium (PTAS) salt has been used for promoting the growth of atomically thin layered materials in chemical vapor deposition (CVD) synthesis. However, the ramifications from the usage of such catalyst are not known comprehensively. Here, we report the influence of PTAS seeding on the transistor device performance from few-layered CVD-grown molybdenum diselenide (MoSe2) flakes. While better repeatability and higher yield can be obtained with the use of PTAS seeds in synthesis, we observed that PTAS-seeded flakes contain particle impurities. Moreover, devices from PTAS-seeded MoSe2 flakes consistently displayed poorer field-effect mobility, current on-off ratio, and subthreshold swing as compared to unseeded flakes.